Flood Hazards in Flat Coastal Areas of the Eastern Iberian Peninsula: A Case Study in Oliva (Valencia, Spain) - Miguel Ángel Eguibar (MDPI AG, 2021)
Enhancing resilience against flooding events is of great importance. Eastern Iberian Peninsula coastal areas are well known for high intensity rainfalls known as DANA or “cold drop”. Extreme records in 24 h can exceed the annual average of the historical series. This phenomenon occurs normally in autumn due to convective storms generated by the existence of cold air in the upper layers of the atmosphere combined with warm winds coming from the Mediterranean Sea. In many coastal areas of the Eastern Iberian Peninsula, their flat topography, sometimes of a marsh nature, and the natural (e.g., dune ridges) and man-made (e.g., infrastructures) factors, result in devastating flooding events of great potential damage and risk for urban and rural areas. In this context, this paper presents the case study of the town of Oliva (Valencia, Spain) and how in a flooding event the flow tends to spread and accumulate along the flat coastal strip of this populated area, causing great potential damage. From that point, the paper discusses the particular issues that flood studies should consider in such flat and heavy rainy areas in terms of the hydrological and hydraulic models to be conducted to serve as the key tool of a correct risk assessment. This includes the correct statistical simulation of rainfalls, the hydrological model dependency on the return period and the correct geometry definition of all possible water barriers. An analysis of the disturbance that climatic change effects may introduce in future flooding events is also performed.